Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen RS St. Elisabeth Semarang - Khasanah, Imroatul; Pertiwi, Octarina Dina (Jurnal Ilmiah Aset, 2010)
The purpose of this research was for analyzing 5 assessments: 1. Effect on the tangible against consumer satisfaction, 2. Effect on reliability against customer satisfaction, 3. Effect on responsiveness on customer satisfaction, 4. Effect on guarantee & certainty against customer satisfaction, 5. Effect on empathy against customer satisfaction. This research has been done with samples taken in random with consideration that the population was very large in numbers, as it wasn’t possible for the surveyor to cover the whole present population, so a representative was formed. Samples in this survey were only a part of the whole community of the city of Semarang that used the services of St. Elisabeth Hospital. Result of this survey shows that these 5 assessments were accepted. The result was, there was a positive and significant relation between tangible of St. Elisabeth hospital, reliability of St. Elisabeth hospital in handling consumer, responsiveness of St. Elisabeth hospital, guarantee & certainty given by St. Elisabeth hospital, empathy against customer satisfaction. This was proved by test F where the value of significance was 0,000, the coefficient of determination on satisfaction shown by Adjusted R Square was 0,716 that means the customer satisfaction was 71,6% affected by variable of tangible, reliability, responsiveness, guarantee and empathy. Whereas, the rest of the 28,4% was affected because other variables were not checked thoroughly by researchers.